ANALISIS MITIGASI KONFLIK GAJAH SUMATRA (Elephas maximus sumatranus, Temmick 1874) DI TAMAN NASIONAL BUKIT BARISAN SELATAN - Luthfi Purwanuriski; Arief Darmawan; Gunardi Djoko Winarno; Indra Gumay Febryano; Ismanto Ismanto; Tri Sugiharti (Jurnal Belantara, 2022)
The conflict between elephants and humans occurs because elephants' habitat is undergoing land conversion to community plants that elephants like. Which causes elephants to enter estate plantations and settlements at night especially when the community's crops are ready to be harvested. This study was conducted to analyze conflict mitigation of elephants and human in Bukit Barisan Selatan National Park. Data was collected by interview survey to the national park officials, conservation partners and affected communities, then this data was analyzed using descriptive analysis. The research was conducted from April to June 2021 at Pemerihan Resort Bukit Barisan Selatan National Park. The results showed that the mitigation carried out by officials, conservation partners and the community was quite effective in driving elephants away from plantations and settlements in the short term. Conflict mitigation is carried out by installing a GPS Collar to monitor the movement of Sumatran elephants so that when the wild elephants approach plantations and settlements, expulsion can be carried out immediately using firecrackers. This mitigation was chosen because it did not injure the elephants. Planting plants that do not like elephants can be done to reduce the occurrence of conflict, in addition to monitoring and further research related to conflict, mitigation needs to be done in order to determine its effectiveness.